The economics of strategy - Besanko, David 1955-; Dranove, David 1956-; Shanley, Mark (Wiley, 1996)
"The book adopts a comprehensive economic point of view, based on the belief that insights from economics can provide a coherent basis for the formulation and evaluation of the external and internal strategies of firms"--Preface.